Transforming public education in Africa, the Caribbean, and the Middle East - Sunal, Cynthia S.; Mutua, Kagendo, 1966-; Odebiyi, Oluseyi Matthew (Research on education in Africa, the Caribbean, and the Middle East., 2019)
Public education has expanded to serve large populations across the regions of Africa, the Caribbean, and the Middle East. Many nations in these regions are moving into a phase of public education in which a variety of factors are being identified as influencing the quality of public education and its ability to serve all children and adolescents. It has become evident that ethnic background, gender, religious affiliation, and ability/disability are important factors in who is served and how well the individual is served. The chapters in this volume, Book 8, of Research on Education in Africa, the Caribbean, and the Middle East document and describe the status, success, and limitations of public education's efforts at transformation. They provide points from which further research and practice might occur.